Endoscopic full-thickness resection in the colorectum: a single-center case series evaluating indication, efficacy and safety - van der Spek, Bas; Haasnoot, Krijn; Meischl, Christof; Heine, Dimitri (Endoscopy International Open, 2018)
Background and study aims Endoscopic full-thickness resection (eFTR) allows en-bloc and transmural resection of colorectal lesions for which other advanced endoscopic techniques are unsuitable. We present our experience with a novel “clip first, cut later” eFTR-device and evaluate its indications, efficacy and safety. Patients and methods From July 2015 through October 2017, 51 eFTR-procedures were performed in 48 patients. Technical success and R0-resection rates were prospectively recorded and retrospectively analyzed.Results Indications for eFTR were non-lifting adenoma (n = 19), primary resection of malignant lesion (n = 2), resection of scar tissue after incomplete endoscopic resection of low-risk T1 colorectal carcinoma (n = 26), adenoma involving a diverticulum (n = 2) and neuroendocrine tumor (n = 2). Two lesions were treated by combining endoscopic mucosal resection and eFTR. Technical success was achieved in 45 of 51 procedures (88 %). Histopathology confirmed full-thickness resection in 43 of 50 specimens (86 %) and radical resection (R0) in 40 procedures (80 %). eFTR-specimens, obtained for indeterminate previous T1 colorectal carcinoma resection, were free of residual carcinoma in 25 of 26 cases (96 %). In six patients (13 %) a total of eight adverse events occurred within 30 days after eFTR. One perforation occurred, which was corrected endoscopically. No emergency surgery was necessary. Conclusion In this study eFTR appears to be safe and effective for the resection of colorectal lesions. Technical success, R0-resection and major adverse events rate were reasonable and comparable with eFTR data reported elsewhere. Mean specimen diameter (23 mm) limits its use to relatively small lesions. A clinical algorithm for eFTR case selection is proposed. eFTR ensured local radical excision where other endoscopic techniques did not suffice and reduced the need for surgery in selected cases.